Analisis Faktor-Faktor Penyebab Kecemasan Matematika - Anditya, Rifin (2016)
Mathematics is a source of technological developments and other sciences. The problem that happens is a lot of students who did not like math as well as indications of mathematics anxiety. Mathematics anxiety adversely affect the implementation and results of learning mathematics. This study aimed to describe the level of mathematics anxiety and find factors that cause mathematics anxiety. The research is a qualitative case study. The subject of research was the 12th Perawat Kesehatan 2 graders of Muhammadiyah Delanggu vocational high school consisting of 26 students. Data collection techniques in this study using questionnaires, interviews, and documentation. Data validation was done with reference materials and member check. Data analysis technique conducted in stages, data reduction, data presentation, and verification or conclusion. The results showed description mathematics anxiety levels that occur in class 12th Health Nurse 2 which 61.54% of the students indicated mathematics anxiety moderate level, 30.77% of the students still can not be categorized as indicated or not indicated mathematics anxiety, and 7.69% of the students who otherwise have no problems with math. Factors that cause mathematics anxiety among mathematics has many formulas, students can not solve mathematical problems, the national examination mathematics, the hope of the family in order to get good grades, conditions of class situation unfavorable, the lack of ability of teachers to convey the subject matter being studied.